Gender Dalam Pendidikan Islam: Sebuah Refleksi - Syaifullah Syaifullah; Sukandi Sukandi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2021)
Gender issues become a very serious issue today. This is identified by a number of discourses on the women’s equal rights and men. Although the actual focus of gender studies is not limited to aspects of women, but also men. But in fact, the figure who is often marginalized is women. On the other hand, men often get more privileges in terms of rights and opportunities. Therefore, this discussion focuses on gender studies of women's aspects by comparing men's rights. Indonesian citizens have the particular rights to receive education, especially Islamic education. This paper designed to describe the problems of gender in education, the theoretical lens of Islamic education on gender equality, as well as the strategy towards gender equality in education.